Crossing the threshold: What motivates individuals who are actively abusing substances to enter treatment? - Peavy, Katherine Michelle (2009)
Although there is an abundance of research in the area of substance abuse, much of it samples people who are already enrolled in treatment. The treatment seeking population may differ from people who are actively using substances. One aim of this study is to describe a sample of individuals who have not sought out treatment, but still actively use substances. Specifically, the investigators assessed 51 county detention facility inmates recently arrested on drug- or alcohol-related charges, examining the factors that both inhibit and promote treatment seeking. We hypothesized that motivation levels for seeking treatment would differ based on several factors: family and social distress, psychological distress, medical problems, severity of drug and alcohol abuse, and primary drug of abuse. Results demonstrated that high levels of psychological distress, as well as distress in one's family/social life, were related to higher levels of motivation for change. We also examined perceived barriers to treatment, which revealed that participants endorsed barriers related to motivation (lack of) and self-perception of drug use. The results of this study have implications for developing brief interventions that could help facilitate the entry of moderately motivated substance users into treatment settings. Shortening the gap between a person's introduction to substance abuse and entrance into treatment could prevent an escalation of substance use that would incur greater consequences, both to the individual user and to society